Antiparkinsonian effect of Nutmeg ethanolic extract (Myristica fragrans Houtt.) in haloperidol-induced Mice - Dwi Hadi Setya Palupi; Isma Galuh Fekhayanti (Pharmaciana, 2024)
Parkinson's disease is a persistent neurological disorder that could potentially arise from the neuronal degeneration responsible for dopaminergic signals in the brain. Extrapyramidal syndrome, which is distinguished by motor dysfunctions including tremors, rigidity, and postural instability, is the defining feature of this disease. One of the contributing factors to the development of Parkinson's disease is drug-induced parkinsonism, which is precipitated by the administration of antipsychotic medications. The bioactive compounds myristicin, eugenol, and flavonoids found in nutmeg (Myristica fragrans Houtt.) have the potential to be utilized in the treatment of Parkinson's disease. The objective of this research endeavor was to ascertain the antiparkinsonian effect of ethanol extract of nutmeg on rodents with Parkinson's disease induced by haloperidol. A seven-day course of induction with haloperidol 1 mg/kg was administered intraperitoneally. Behavioral evaluations were conducted utilizing the cylinder and rotarod tests. Cylinder score and latency time were utilized to evaluate extrapyramidal symptoms. The therapeutic approach involved the oral administration of ethanol extract of nutmeg in varying concentrations (5, 10, and 20 mg/kg) over a period of seven days. The findings indicated that the administration of nutmeg at a rate of 20 mg/kg resulted in noteworthy enhancements (P < 0.05) in the motor function of animal models induced by haloperidol. Furthermore, this effect was comparable to that of the standard drug Pramipexole.